Kindergarten Dinosaurs and Rocks: An Example of Integrating a Field-tested Lesson Plan for Geoscientists into the Alberta Curriculum - Stancliffe, R.; Mann, D.; Mann, G. (Geoscience Canada, 2006)
SUMMARY Professional geoscientists have to make many presentations to colleagues, engineers, executives and accountants. However, panic is often felt when a note comes home from a child's educator looking for parents to help in teaching elementary school students. For the teacher, this is a chance to integrate many core subjects from the curriculum with the special and exciting resources available to geoscientists. This paper presents guidelines developed over time, and includes an understanding of how children learn and ask questions, the pace of the talk, and what children need to learn. In addition, data sources and gateways available to geoscientists have been included. While the premise outlined in the paper is applicable across Canada, it is based on the Alberta curriculum requirements. With these suggestions, the classroom experience is really no different than presenting to senior management, although you have to remember that your audience is shorter and does not drive a big BMW or Lexus.